Field reports form, contributed by Jim L. Fuller, fall 1986 - Fuller, James L.et al (1986)
Fuller lists various birds sighted during the fall season, including an albino Barred Owl. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly Report of fall 1986. Epson - sheet feed